2022
DOI: 10.1016/j.jmmm.2021.168928
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of finite magneto-electric coupling in SmFeO3 – PbTiO3 solid solutions

Abstract: Present work investigates the detailed multiferroic properties of Pb1-xSmxTi1-xFexO3, (x = 0.21, 0.22, 0.23, 0.24 and 0.25) synthesize through solid state reaction route. The structural, dielectric, ferroelectric and magnetic properties were measured. A sincere study is carried out to detect the magneto-electric coupling in all the samples through magneto-dielectric, magnetization after electric poling and magneto-pe response. The maximum value of coupling coefficient (γ) and magneto-dielectric response (MDR) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…[12][13][14] Several studies have been done in this approach where PbTiO 3 -ReFeO 3 have been analyzed for its magnetoelectric coupling within the single structure. [15][16][17] From the literature survey, we have found that PbTiO 3 shows 11.56%, 13.09% and 33.7% change in the dielectric constant when doped with PrFeO 3, SmFeO 3 and NdFeO 3 respectively. Therefore, Nd doped PT has been decided for the perovskite part.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Several studies have been done in this approach where PbTiO 3 -ReFeO 3 have been analyzed for its magnetoelectric coupling within the single structure. [15][16][17] From the literature survey, we have found that PbTiO 3 shows 11.56%, 13.09% and 33.7% change in the dielectric constant when doped with PrFeO 3, SmFeO 3 and NdFeO 3 respectively. Therefore, Nd doped PT has been decided for the perovskite part.…”
mentioning
confidence: 99%
“…Owing to its high Curie point, which also relies on composition, high electric resistivity, high magnetic permeability, low dielectric loss, superior chemical stability, and heat treatment of the samples, Sr-hexaferrites are among the most adaptable and materials that are appropriate for both low-frequency and high-frequency equipment are used. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It is worth mentioning that the Interface of particles or grain does play important role in these kinds of composites in nano particles based thin films. The required correlation of charge, spin, orbital, and lattice freedom degrees frequently puts demanding constraints on deposition circumstances, and interface engineering in complicated oxide thin films has inspired several novel room-temperature functions.…”
mentioning
confidence: 99%